An Indicator contribution-oriented assessment framework for identifying dominant fire risk drivers in cable tunnels: Development and case study - Liming Li; Yongyu Wang; Bo Liu; Liwei Song; Wentao Ma (PLoS ONE, 2026)
Cable tunnels are critical components of urban power supply systems, where fire incidents can cause severe safety consequences due to high cable density and confined environments. Effective fire risk management is challenged not only by risk quantification, but also by limited understanding of which factors dominantly drive fire risk variation across tunnel segments.This study proposes a contribution-oriented fire risk assessment framework for cable tunnels that integrates hierarchical indicator weighting with indicator contribution analysis. A structured fire risk indicator system is established based on fire accident mechanisms, engineering standards, and expert knowledge. A composite fire risk index is calculated for segmented tunnel units, and a perturbation-based contribution analysis is conducted to quantify the marginal influence of individual indicators on overall risk levels. Scenario-based analyses are further employed to examine the effectiveness of alternative fire prevention and management strategies. A case study shows that cable tunnel fire risk is governed by a limited number of dominant drivers rather than uniform contributions from all indicators. Structural integrity–related factors, such as fire door integrity and joint defects, together with key operational and management indicators, exhibit the strongest influence on fire risk formation. The results also reveal pronounced spatial heterogeneity in fire risk distribution and differentiated responses to management interventions. By identifying dominant fire risk drivers and their contribution characteristics, the proposed framework enhances the interpretability and practical value of fire risk assessment, supporting targeted risk control and resource prioritization in cable tunnel safety management.